Relationship between guilt, shame and treatment motivation in individuals with opioid addiction - Caymaz, Nuray; Ceylan, Melike (Journal of Dependence, 2024)
Objective: This study aims to identify best practices in combating addiction by thoroughly examining the relationship between opioid addiction and feelings of guilt, shame, and treatment motivation.Method: The sample of the study consists of 288 patients diagnosed with opioid addiction according to DSM-5 criteria by psychiatrists at Balıklı Rum Hospital. The scales used in the study were the Sociodemographic Form, the Guilt-Shame Scale, and the Treatment Motivation Questionnaire.Results: There is a significant relationship between the level of guilt and internal motivation, confidence in treatment and treatment motivation and between shame and internal motivation and general treatment motivation. When the regression coefficients are analyzed, it is seen that only guilt scores are a significant predictor of treatment motivation scores. The shame variable does not have a significant effect. The participants' mean scores of guilt were found to be significantly higher than their mean scores of shame.Conclusion: The study revealed a significant link between guilt and various aspects of treatment motivation, while shame showed a less pronounced association. Participants reported higher mean scores for guilt compared to shame, emphasizing the potentially greater relevance of guilt in influencing treatment motivation. Focusing on psychodrama and psychoeducational group studies for the treatment of opioid addiction can make it easier for the individual to express difficult negative emotions and develop awareness within the group.
Keywords: Opioid addiction; guilt; shame; treatment motivation